2004
DOI: 10.1111/j.1464-410x.2004.04819.x
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of tadalafil: an update

Abstract: OBJECTIVE To provide an update on the efficacy and safety of tadalafil, a phosphodiesterase‐5 inhibitor, in the treatment of erectile dysfunction (ED). PATIENTS AND METHODS In all, 2102 men (mean age 56 years) with mild‐to‐severe ED of various causes were randomized to placebo or tadalafil, taken as needed with no food restrictions, at fixed ‘on‐demand’ doses of 10 or 20 mg in 11 randomized, double‐blind, placebo‐controlled trials lasting 12 weeks. The three co‐primary outcomes were changes from baseline in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
173
3
14

Year Published

2004
2004
2013
2013

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 186 publications
(219 citation statements)
references
References 18 publications
29
173
3
14
Order By: Relevance
“…Compared with sildenafi l and vardenafi l, tadalafi l is much less inhibitory for PDE6, and it is over 700 times more potent for PDE5 than PDE6 (ICOS 2008). For this reason, tadalafi l has less than 0.1% occurrence of vision abnormalities (Brock et al 2002;Carson et al 2004a).…”
Section: Phosphodiesterase Selectivitymentioning
confidence: 99%
See 4 more Smart Citations
“…Compared with sildenafi l and vardenafi l, tadalafi l is much less inhibitory for PDE6, and it is over 700 times more potent for PDE5 than PDE6 (ICOS 2008). For this reason, tadalafi l has less than 0.1% occurrence of vision abnormalities (Brock et al 2002;Carson et al 2004a).…”
Section: Phosphodiesterase Selectivitymentioning
confidence: 99%
“…A large study of 2102 men from 11 different multicentered, randomized, double-blind, placebo controlled trials of tadalafi l reported the drug is well tolerated overall (Carson et al 2004a). Fifty-one percent of men using tadalafi l 20 mg had at least one adverse event (AE), but only 3.2% discontinued treatment.…”
Section: Adverse Eventsmentioning
confidence: 99%
See 3 more Smart Citations